Measurements of the Total and Differential Higgs Boson Production Cross Sections Combining the H→γγ and H→ZZ*→4ℓ Decay Channels at $\sqrt{s}$=8 TeV with the ATLAS Detector - ATLAS collaboration (2822 authors) (2019)
Submitted by Helmut Wolters (helmut@coimbra.lip.pt) on 2019-02-04T06:47:03Z No. of bitstreams: 2 1.pdf: 1111909 bytes, checksum: 73a53c7ede5c783143a30ffe91086ee4 (MD5) zip/1364361.zip: 761781 bytes, checksum: 247e3794f09453bfb5a294ff459ce598 (MD5)